1975
DOI: 10.1254/jjp.25.383
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Diltiazem on Electrical and Mechanical Activity of Isolated Cardiac Ventricular Muscle of Guinea Pig

Abstract: Abstract-Diltiazem, a new 1,5-benzothiazepine derivative, antagonized calcium ion and thus caused a reduction in the contractile force of isolated papillary muscle. The antagonistic ratio of diltiazem to calcium ion was estimated to be approx. 1 : 100. A lower concentration of diltiazem (2.2 yX 10-13 M) decreased the contractile force without affecting significantly the intracellularly recorded resting and action potentials. When the concentration of the compound was increased to 2.2 x 10-5 M, only the maximum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
48
0

Year Published

1976
1976
1999
1999

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 174 publications
(51 citation statements)
references
References 32 publications
3
48
0
Order By: Relevance
“…The experimental procedures were similar to those described in the previous papers (1,13 Similar results were also obtained when stimulus of a low frequency (0 .2 Hz) was applied to the preparation at CaC12 concentration ranging from 0.6 to 7.8 mM.…”
Section: Methodssupporting
confidence: 66%
See 1 more Smart Citation
“…The experimental procedures were similar to those described in the previous papers (1,13 Similar results were also obtained when stimulus of a low frequency (0 .2 Hz) was applied to the preparation at CaC12 concentration ranging from 0.6 to 7.8 mM.…”
Section: Methodssupporting
confidence: 66%
“…It was also suggested that the compound antagonizes calcium ion essential for muscle contraction, thus causing a reduction in the contractile force of the myocardium (1). On the other hand, it has been reported that the slow inward calcium or calcium-sodium current, as well as the fast inward sodium current, is involved in the generation of the action potential of cardiac muscle fibers under normal physiological conditions (4)(5)(6)(7)(8)(9)(10)(11)(12)(13).…”
mentioning
confidence: 99%
“…In isolated myocardium (7,8) and vascular (9)(10)(11)(12) or intestinal (13)(14)(15)(16) smooth muscles, it has been reported that this compound antagonizes calcium ion which is essential for muscle contraction, thus producing a decrease in the contractile force. Such a calcium antagonistic property of diltiazem has been shown in isolated pancreatic B-cell (1): the glucose-induced insulin secretion from the isolated islets of Langerhans from rats was suppressed by diltiazem and this effect was counteracted by increasing extracellular concentration of calcium ion.…”
Section: Discussionmentioning
confidence: 99%
“…In another series of supplemental experiments, in order to study the effects of calcium (Ca++) channel blocker on production of VT in ten dogs other than the above 15 dogs, LCX injection was carried out following intravenous infusion over a 4 min of diltiazem hydrochloride (Nakajima et al 1975), in a dose of 1 mg/kg body weight.…”
Section: Methodsmentioning
confidence: 99%